Call of the sound dragon - West, Tracey, 1965-; Loveridge, Matt (New York, NY : Scholastic Inc., 2020)
The city of Remus is being torn apart by a duel between two wizards, and Drake, Petra, and Griffith have traveled there to assist a blind dragon master, Tessa, in sorting out the situation; using the sound dragon's unique power to manipulate sound waves, the dragon masters retrieve the Power Crystal which is embedded inside an unbreakable rock, but will it be able to absorb the cloud of uncontrolled magic that is threatening the city before it is too late?
K-3
540L
Keywords: Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Wizards -- Juvenile fiction; Dueling -- Juvenile fiction; Adventure stories; Dragons -- Fiction; Magic -- Fiction; Wizards -- Fiction; Dueling -- Fiction; Fantasy; Adventure and adventurers -- Fiction; Action and adventure fiction; Fantasy fiction